LEGAL ASPECTS ON DIVORCE ON CHILDREN - Choudhury, Pankaj; Sharma, Vikas; Singh, Kritika (International Journal of Psychosocial Rehabilitation, 2020)
Lord Penzance defined marriage as "the consensual union for life of one man and one woman to the exclusion of all others" as one of the oldest institutions in human history. It's important to keep in mind that once a marriage has irretrievably broken down, it becomes a source of potentially intractable legal and societal issues. Even if a couple is eager to end their marriage and get a divorce, the question of how to protect the interests of the couple's children in the event of a divorce can cause seemingly insurmountable social challenges. There are many challenges and problems that arise when a marriage fails, and the purpose of this study is to examine them critically in order to provide for the emotional, social, psychological, physical, and moral well-being of the children of such a marriage that has ended in divorce. A comparative confluence between the psychology of divorce and the law will be created by analysing the existing laws of the Matrimonial Causes Act, which govern divorce and custody, using analytical, critical, historical, and empirical methods.